2013
DOI: 10.4049/jimmunol.1202284
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of CCL15 Expression and Monocyte Adhesion to Endothelial Cells (ECs) after Hypoxia/Reoxygenation and Induction of ICAM-1 Expression by CCL15 via the JAK2/STAT3 Pathway in ECs

Abstract: CCL15, a member of the CC chemokine family, is a potent chemoattractant for leukocytes and endothelial cells (ECs). Given that chemokines play key roles in vascular inflammation, we investigated the effects of hypoxia/reoxygenation (H/R) on expression of human CCL15 and a role of CCL15 in upregulating ICAM-1 in ECs. We found that exposure of ECs to H/R increased expression of CCL15 and ICAM-1, which resulted in an increase in monocyte adhesivity to the ECs. Further studies revealed that knockdown of CCL15 or C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 43 publications
3
30
0
2
Order By: Relevance
“…3), it was not upregulated after radiation exposure in vivo (Fig. 4), which suggests a role for the tumor microenvironment in ICAM-1 regulation, in agreement with other reports [36]. Further, no significant differences in APM modulation in vivo were observed between fractionated (2 Gy × 5) and single dose (10 Gy × 1) radiation.…”
Section: Discussionsupporting
confidence: 90%
“…3), it was not upregulated after radiation exposure in vivo (Fig. 4), which suggests a role for the tumor microenvironment in ICAM-1 regulation, in agreement with other reports [36]. Further, no significant differences in APM modulation in vivo were observed between fractionated (2 Gy × 5) and single dose (10 Gy × 1) radiation.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we found 1 h Hypoxia/2 h reoxygenation increased ICAM-1 and E-Selectin protein expression. Our data were consistent with previous studies [21][22][23] which indicated that Hypoxia (range from 1 to 2 h)/reoxygenation (range from 1 to 3 h) could increase endothelial adhesion molecule expression at protein and mRNA level. These findings indicated that 2-3 h H/R was sufficient to induce endothelial adhesion molecule expression.…”
Section: Discussionsupporting
confidence: 95%
“…ICAM-1 activates leukocytes and endothelial cells (ECs), which in turn prompt the release of various inflammatory mediators, resulting in systemic inflammatory response syndrome (SIRS), acute respiratory distress syndrome (ARDS) and multi-organ dysfunction syndrome (MODS)[48]–[51]. The present results showed that CORM-2 inhibits the increase of ICAM-1 expression in LPS-stimulated HUVECs.…”
Section: Discussionmentioning
confidence: 58%